GENERAL REMARKS REGARDING THE LAWYER PROFESSION WITHIN THE EUROPEAN UNION - AUGUSTIN FUEREA (Challenges of the Knowledge Society)
Legal professions are generally regulated at national level. Although there may be natural similarities between them, these national regulations differ quite substantially from one country to another. The effective exercise by lawyers of the freedom to provide services is governed by the provisions of Directive 77/249/EEC. Lawyers established in the EU may offer their services on a temporary basis in any EU country. However, they must retain their home-country professional title, expressed in the language (or one of the languages) of that country.